Pengaruh Retribusi Pelayanan Pasar Dan Retribusi Pelayanan Parkir Terhadap Peningkatan PAD Kabupaten Mamuju - Halim, Abdul; Ratna, Ratna (LPPM Universitas Muhammadiyah Mamuju, 2022)
This research takes the title The Effect of Market Service Charges and Parking Service Fees on Increasing Regional Original Income in Mamuju Regency. The purpose of this research is to analyze the significance of the effect of market service levies and parking service fees partially on increasing Mamuju Regency's Original Regional Revenue and to analyze the significance of the effect of market service levies and parking service levies simultaneously on increasing Mamuju Regency's Original Revenue. The results showed that the variables of Market Service Charges and Parking Service Charges partially had no significant effect on Regional Original Revenue of Mamuju Regency, because the average contribution of Market Service Charges each year was only 1.19 percent, and the average contribution of Parking Service Charges each year only 0.22 percent. Based on the results of the f test, it can be stated that both the market service levy variable and the parking service levy simultaneously or simultaneously can be stated that it has an effect but is not significant on Mamuju Regency's Original Revenue